2020
DOI: 10.29333/ejgm/7881
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Nurses’ Perception of the Causes of Ageism in Hospital Settings

Abstract: Given the aging population increase, providing quality care to the elderly is one of the major challenges of health care systems. The purpose of the present study is to explain the perception of nurses about the causes of ageism in providing hospital care to the elderly referred to hospital settings in the city of Tehran. Methods: The study utilized a qualitative design with individual interviews and with Conventional Content Analysis Approach. In this qualitative study, participants were selected through a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The findings of the study by Hosseini et al (2020) indicated that the evaluation of care for the older adults by family members, society and the care provider system has a positive effect on the acceptance and provision of quality care for the older adults [42]. The results of another study in this field indicated that effective supervision of geriatric specialist in the training of experienced personnel, spending enough time and money can be effective in providing quality care and prevent the marginalization of this age group in the health care system [10]. Liu also stated in his findings that having a positive attitude towards the older adults has led to the creation of a management system in the hospital that reduces ageism [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study by Hosseini et al (2020) indicated that the evaluation of care for the older adults by family members, society and the care provider system has a positive effect on the acceptance and provision of quality care for the older adults [42]. The results of another study in this field indicated that effective supervision of geriatric specialist in the training of experienced personnel, spending enough time and money can be effective in providing quality care and prevent the marginalization of this age group in the health care system [10]. Liu also stated in his findings that having a positive attitude towards the older adults has led to the creation of a management system in the hospital that reduces ageism [43].…”
Section: Discussionmentioning
confidence: 99%
“…One of the barriers is the presence of negative stereotypes and attitudes towards aging that may reduce the efficiency and quality of these services [9]older adultsolder adults. In fact, community members believe that illness and disability are often associated with old age and the older adults do not need to be cared for [10,11]. There has also been evidence of ageism in terms such as the boomer remover in relation to Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are the largest group of healthcare providers to older adults in hospitals (Melia & Choowattanapakorn 2016). Moreover, studies report the existence of ageism in older adult care (Liu, Norman & While 2015;Mehri et al, 2020a). Studying ageism in hospitals can increase the nurses' knowledge and awareness of ageism (Cowan…”
Section: Introductionmentioning
confidence: 99%